A Cross-sectional Study on Internet Gaming Disorder and Its Association with Personality Traits in Engineering Students - Mohamed Imran H; Sharan Roy Chowdhury; Indla Ramasubba Reddy; Sayan Maji (Indian Journal of Psychological Medicine)
Background: In the field of psychiatry and mental health, Internet gaming disorder (IGD) is a relatively new concept. In the past few decades, as online gaming and internet usage became increasingly prevalent, this became a topic of concern and research. Therefore, this study aims to estimate the prevalence of IGD and its association with personality traits among students. Methods and material: The present cross-sectional study was conducted at an Engineering college in Nunna, Andhra Pradesh. The planned duration of the study was 12 months, from March 2020 to March 2021. However, it was extended until August 2021 due to the COVID-19 pandemic lockdown, as colleges were closed indefinitely until further instructions. In the current study, a total of 170 students (first year to final year) from an engineering college, aged between 19 and 25 years, were included. Students who provided informed consent or expressed willingness to participate in the study through a self-structured questionnaire and those who had internet access or experience with online gaming in the past 12 months were included. The demographic profile, including age, sex, academic year, accommodation status, and departmental course was studied. Also, the device used for gaming was examined. Results: The gender distribution in the given population indicates that approximately 65.88% are males and 34.12% are females, for a total of 170 individuals studied. In that 18 participants (10.58%) were found to have IGD. Among 18 participants with IGD, 14 were males and 4 were females. The gender prevalence for male and female participants was calculated separately and found to be 12.5% for males, and 6.9% for females which is almost a ratio of 2:1. The summary explores the relation between the Big Five personality traits and IGD. The current study subjects were categorized as low, medium, or high for each trait based on their IGD status (positive or negative). Significant correlations were determined between extraversion and IGD ( p = .02), conscientiousness and IGD ( p = .02), and neuroticism and IGD ( p = .02). Conclusion: The current study findings suggest that the overall prevalence of IGD among college students is 10.58% with a higher prevalence among males, IGD is positively connected with neuroticism and negatively correlated with extraversion and conscientiousness. This implies that certain characteristics, either alone or in combination, may raise the likelihood of individuals developing an IGD.